Uji Efektivitas Analgetik Ekstrak Etanol Daun Sirih Merah (Piper crocatum) pada Mencit Putih (Mus musculus L) yang Diinduksi dengan Asam Asetat - Hasna Adwa Salsabila Nursantoso; Muhammad Walid (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study explored the analgesic effectiveness of ethanol extract of red betel leaf (Piper crocatum) in white rats (Mus musculus L.) induced with acetic acid. A total of 15 rats were divided into five groups with different treatments, and the number of twitching movements as a pain response was measured for one hour. The extract was prepared using 96% ethanol solvent, and the analgesic effect was analyzed using the writhing test method. The results showed that the extract contained flavonoids, alkaloids, tannins, and saponins, which might contribute to its analgesic properties. It was found that the higher the dose of extract administered, the greater the inhibition of pain that occurred, with a dose of 800 mg/kgBB showing optimal analgesic effectiveness, almost equivalent to paracetamol as a positive control. Statistical analysis showed significant differences between treatment groups, with doses of 200 mg/kgBB and 400 mg/kgBB showing lower effectiveness. This study recommends further exploration of the therapeutic benefits of red betel leaf extract and formulation development for wider medical applications.